Sistem Informasi Manajemen VPN Remote Mikrotik Berbasis Codeigniter PHP Framework Di Desa Sawo - E, Poerbaningtyas; Adi, Achmad Riyan (LPPM STIKI MALANG, 2024)
Managing VPN accounts and configuring port forwarding on a Mikrotik CHR (Cloud Hosted Router) using Winbox is a complicated task for ordinary users who have no experience in network administration. So the configuration impacts include errors in determining TCP/UDP, Firewall Rules, IP and port numbers which result in port conflicts because the remote VPN fails to be managed properly. Based on the existing problems, the researchers created a Management Information System to manage forwarding, VPN accounts, payment gateways. So it will minimize human error and be more effective in automating configuration with a more attractive interface. This is useful for making it easier to use port forwarding on the Mikrotik CHR. The website-based VPN management system application uses the Mikrotik API and the type of VPN used is only L2TP/IPSec site-to-site protocol remote access. This research can increase productivity in managing VPN accounts and port forwarding.